Transauricular vagus nerve stimulation for patients with disorders of consciousness: A randomized controlled clinical trial - Zhou, Yi-Fan; Kang, Jun-Wei; Xiong, Qi; Feng, Zhen; Dong, Xiao-Yang (Frontiers in Neurology, 2023)
Introduction Disorders of consciousness (DoCs) are a frequent complication of brain injury disease, and effective treatments are currently lacking. Transauricular vagus nerve stimulation (tVNS) has been proposed as a promising therapeutic method for neurological disorders such as epilepsy and depression. In our previous study, we demonstrated that vagus nerve stimulation promoted recovery in rats with DoCs caused by traumatic brain injury. However, the clinical effect of vagus nerve stimulation on consciousness disorders is unclear. We aimed to investigate the therapeutic efficacy and safety of tVNS in patients with DoCs. Methods We conducted a randomized, double-blinded, sham-controlled trial. Patients (N = 60) with DoCs, including minimally conscious state (MCS) and vegetative state/unresponsive wakefulness syndrome, were enrolled and randomized to groups receiving either active or sham tVNS. A frequency of 20 Hz and pulse wave of 200 us was used in the active-tVNS protocol, which was performed in the auricular branch of the vagus nerve in the left outer ear. The sham-tVNS protocol was the same as the active-tVNS protocol although without current input. Both groups of patients also received conventional treatments. Consciousness was evaluated according to the Coma Recovery Scale-Revised before and after the 4-week intervention. We also recorded the type and number of behavioral responses. Safety was primarily assessed according to the incidence of treatment-emergent adverse events. Each patient's heart rate and blood pressure were monitored during all treatment sessions. Results Ultimately, 57 patients completed the study: 28 patients underwent active tVNS and 29 patients underwent sham tVNS. No significant differences were observed in Coma Recovery Scale-Revised scores between the active- and sham-tVNS groups before the tVNS sessions. Compared with patients in the sham-tVNS group (9.28 ± 4.38), patients with DoCs treated with active tVNS showed improved consciousness (10.93 ± 4.99), although not statistically significant. Further analysis revealed obvious differences between patients with MCS receiving active and sham tVNS, but no significant difference in patients with vegetative state/unresponsive wakefulness syndrome in both groups. All side effects were considered common medical conditions with no obvious correlation to tVNS. Conclusion These preliminary data provide early evidence that tVNS may be an effective and safe approach for promoting the recovery of consciousness, especially in patients with MCS. Clinical trial registration https://www.chictr.org.cn/edit.aspx?pid=175938&htm=4, identifier: ChiCTR2200066629.